2013
DOI: 10.1177/0951484813481589
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and transformational change in healthcare organisations: A qualitative analysis of the North East Transformation System

Abstract: The research project 'An Evaluation of Transformational Change in NHS North East' examines the progress and success of National Health Service (NHS) organisations in north east England in implementing and embedding the North East Transformation System (NETS), a region-wide programme to improve healthcare quality and safety, and to reduce waste, using a combination of Vision, Compact, and Lean-based Method. This paper concentrates on findings concerning the role of leadership in enabling tranformational change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Previous studies of health systems transformation have identified factors that are key to the successful implementation of policy, including supportive organisational culture, cooperative interorganisation networks, clear communication and a willingness to engage with systems leaders 17. Our key findings echo those reported in an earlier ambitious transformational change initiative undertaken in the North East of England 26. This occurred prior to the major structural changes imposed on the NHS as a consequence of the Health and Social Care Act 2012, and had it not been for that disruptive legislation the initiative would have continued as there was a high degree of commitment to it and a significant investment of resources and political and managerial capital.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies of health systems transformation have identified factors that are key to the successful implementation of policy, including supportive organisational culture, cooperative interorganisation networks, clear communication and a willingness to engage with systems leaders 17. Our key findings echo those reported in an earlier ambitious transformational change initiative undertaken in the North East of England 26. This occurred prior to the major structural changes imposed on the NHS as a consequence of the Health and Social Care Act 2012, and had it not been for that disruptive legislation the initiative would have continued as there was a high degree of commitment to it and a significant investment of resources and political and managerial capital.…”
Section: Discussionsupporting
confidence: 79%
“…It was certainly a key factor throughout the NETS at all levels and across all organisations in our case study sites. 148 The Pettigrew et al 125 'receptive contexts for change' framework includes as one of the eight factors 'key people leading change'. The words were deliberately chosen to avoid connotations of heroic and individualistic 'macho managers'.…”
Section: The Importance Of Leadership and Its Effectivenessmentioning
confidence: 99%
“…The NETS would not have been conceived or happened if a handful of key people in NHS North East had not had the vision and commitment to see it happen (Erskine et al, 2013). These individuals largely remained together over a period of years to provide continuity and consistency of purpose.…”
mentioning
confidence: 99%